Clinical-Grade Oncolytic Adenovirus Purification Using Polysorbate 20 as an Alternative for Cell Lysis - Moleirinho, Mafalda G.; Rosa, Sara; Carrondo, Manuel J.T.; Silva, Ricardo J.S.; Hagner-McWhirter, Åsa; Ahlén, Gustaf; Lundgren, Mats; Alves, Paula M.; Peixoto, Cristina (Current Gene Therapy, 2018)
Introduction: Oncolytic virus therapy is currently considered as a promising therapeutic approach for cancer treatment. Adenovirus is well-known and extensively characterized as an oncolytic agent. The increasing number of clinical trials using this virus generates the demand for the development of a well-established purification approach. Triton X-100 is commonly used in cell lysis buffer preparations. The addition of this surfactant in the list of substances with the very high concern of the Registration, Evaluation, Authorization and Restriction of Chemicals (REACH) regulation promoted the research for effective alternatives. Methods: In this work, a purification strategy for oncolytic adenovirus compatible with phase I clinical trials, using an approved surfactant – Polysorbate 20 was developed. The proposed downstream train, composed by clarification, concentration using tangential flow filtration, intermediate purification with anion exchange chromatography, followed by a second concentration and a final polishing step was evaluated for both Triton X-100 and Polysorbate 20 processes. The impact of cell lysis with Polysorbate20 and Triton X-100 for each downstream step was evaluated in terms of product recovery and impurities removal. Overall, 61 ± 4% of infectious viral particles were recovered. Depletion of host cell proteins and ds-DNA was 99.9% and 97.1%, respectively. Results & Conclusion: The results indicated that Polysorbate 20 can be used as a replacement for Triton X-100 during cell lysis with no impact on product recovery, potency, and purity. Moreover, the developed process is scalable and able to provide a highly purified product to be used in phase I and II clinical trials.
Keywords: GMP process development